Single Market Emergency Instrument – A Tool with Pitfalls - Samina Sultan; Christian Rusche; Hubertus Bardt; Berthold Busch (Intereconomics, 2023)
In reaction to disruptions of the Single Market, the European Commission put forward an emergency instrument. It proposes far-reaching measures in order to maintain the proper functioning of the Single Market and ensure the supply and distribution of goods and services. The dirigiste interventions in the market it enables warrant critical review, while better coordination and information exchange between the member states could be an added value of the Single Market Emergency Instrument.
Keywords: F15; H12; O52; 330; EU internal market; internal EU trade; foreign trade; stabilization policy; crisis management; EU countries; EU-Binnenmarkt; EU-Binnenhandel; Außenhandel; Stabilisierungspolitik; Krisenmanagement; EU-Staaten